2019
DOI: 10.1093/europace/euz061
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transcatheter mitral valve repair on ventricular arrhythmias

Abstract: Aims Patients with heart failure and severe mitral regurgitation (MR) have a poor prognosis and carry an increased risk for ventricular arrhythmias. The present study evaluates the impact of transcatheter mitral valve repair using the MitraClip on the potential reduction of ventricular arrhythmias. Methods and results Patients undergoing MitraClip implantation were prospectively enrolled into the present study and received 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 19 publications
1
16
1
Order By: Relevance
“…A reduction in the incidence of VA and ICD therapies after successful PMVR were found in a small cohort of patients with HFrEF and FMR who had either a pacemaker, ICD or CRT implanted (9). Similarly, Ledwoch et al (10) documented by 24-hour electrocardiographic monitoring a reduction in ectopic ventricular activity, NSVT and SVT at 6-month follow-up after PMVR. Whether these changes have any impact on mortality, has not been evaluated.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A reduction in the incidence of VA and ICD therapies after successful PMVR were found in a small cohort of patients with HFrEF and FMR who had either a pacemaker, ICD or CRT implanted (9). Similarly, Ledwoch et al (10) documented by 24-hour electrocardiographic monitoring a reduction in ectopic ventricular activity, NSVT and SVT at 6-month follow-up after PMVR. Whether these changes have any impact on mortality, has not been evaluated.…”
Section: Discussionmentioning
confidence: 79%
“…Percutaneous mitral valve repair (PMVR) with MitraClip ® (Abbott Vascular, Santa Clara, USA) has proved to effectively reduce FMR in patients with HFrEF (8). Limited information has been reported regarding the impact of PMVR on VA burden (9,10). The aim of this study was to address the incidence of VA and appropriate antitachycardia pacing (ATP) and defibrillation shocks before and after PMVR in patients with HFrEF, FMR and implantable cardiac devices (ID).…”
Section: Introductionmentioning
confidence: 99%
“…Ledwoch et al [ 50 ] recently demonstrated in a prospective study using MitraClips in patients with heart failure and severe MR (82% had secondary MR) a significant reduction in ventricular arrhythmias (nsVT and sustained ventricular tachycardia (sVT)). They were reduced from 32% to 14% at follow-up ( p = 0.01), and the PVC decreased from 16% to 4% ( p = 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…The application of the ToVAMI concept in the current ICD population was feasible and increased the rate of identified triggers and the rate of optimized heart failure treatment. This is mainly due to the recent development of new prognostic drugs or interventional therapies which offer new perspectives in the treatment of heart failure (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic heart failure treatment such as valsartan/sacubitril, CRT (cardiac resynchronization therapy) or Mitra-Clip are known to improve the survival of patients with heart failure while reducing the rate of sudden cardiac death and the occurrence of ventricular arrhythmias (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%